Space Weather and Challenges for Modern Society. Issue 1 (28th January 2013) - Brekke, Pål; Steen, Roger; Onsager, Terry; Wintoft, Peter; Olaussen, Alf; Pirjola, Risto; Stauning, Peter; Sundelius, Bengt; Ohnstad, Trond; Marti, Luis
Key Points: Meeting summary after the OSLO TIEMS Space Weather Conference